Video or audio listening tests for English language teaching context: which is more effective for classroom use? - Clara Herlina Karjo; Menik Winiharti; Safnil Arsyad (JOALL (Journal of Applied Linguistics and Literature), 2022)
Multimodal inputs (both auditory and visual) in the forms of films and videos have long been used in teaching EFL listening comprehension. Previous studies have shown that listening while watching videos can significantly aid students’ comprehension. However, videos were rarely used as testing materials since they contained more than aural input so they did not ‘really’ test listening. This study explored the extent to which multimodal testing materials can be used in testing listening comprehension for EFL students and how the results would differ from that of mono modality testing materials. The participants were 100 students of the English Department, Bina Nusantara University (henceforth Binus) University Jakarta. The researchers gave them two kinds of tests: the video listening test (VLT) and audio listening test (ALT). The materials were two short videos from YouTube. The first test, ALT was given after the participants listened to the videos twice. On the contrary, VLT was administered after they watched the videos twice. To examine the differences in the effects of VLT or ALT on EFL students’ performance in listening comprehension, the data were analyzed quantitatively. The results indicate that students got better scores for VLT compared to ALT. The findings imply that students’ performance in listening comprehension is significantly improved with multimodal testing materials